INFLUENCE OF HYPOTHYROIDISM ON PREGNANCY AND FETAL DEVELOPMENT: A COMPREHENSIVE INVESTIGATION OF THE RISKS, MECHANISMS AND MANAGEMENT STRATEGIES WITH LEVOTHYROXINE SODIUM - Pardinho, Lethícia Costa; Tavares, Barbosa; Oliveira, Hudson Vasconcelos de; Oliveira, Ane Beatriz Jesus; Tavares, Renata Barbosa; Rezende, ⁠Eduardo Henrique Mendes; Filho, Murilo Dell Eugenio Costa; Ananias, Mariana Millena Pereira; Sandes, Thayssa Souza; Andrade, Carolina Ázara; Silva, Fernanda Rego da; Ferrari, Isadora Pedroche; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Pregnancy is a critical period in which maternal health directly influences fetal development. Hypothyroidism, a condition characterized by insufficient production of thyroid hormones, can have a significant impact on this process. We investigated the risks, mechanisms and management strategies of hypothyroidism during pregnancy, focusing on the administration of levothyroxine sodium. This topic is crucial due to the potential adverse effects of untreated hypothyroidism on the mother and fetus, including complications such as miscarriage, pre-eclampsia, premature birth and deficits in the neurological development of the fetus. Objective: To conduct a systematic review of the literature to analyze the effects of hypothyroidism on pregnancy and fetal development, evaluate the effectiveness of levothyroxine sodium as a management strategy, and identify gaps in knowledge to guide future research. Methodology: Using the PRISMA checklist, the PubMed, Scielo and Web of Science databases were searched for articles published in the last 10 years. The descriptors used were "hypothyroidism", "pregnancy", "fetal development", "levothyroxine sodium" and "management". The inclusion criteria were original studies published in English, Portuguese or Spanish that investigated the effects of hypothyroidism on pregnancy and fetal development, as well as the effectiveness of levothyroxine sodium as a treatment. Exclusion criteria were duplicate studies, literature reviews and studies with small samples or inappropriate methodologies. Results: The studies reviewed highlighted the impacts of hypothyroidism during pregnancy, including an increased risk of obstetric complications and adversities in fetal development. Levothyroxine sodium has been shown to be effective in normalizing maternal hormone levels and reducing these risks, although questions about dosing and monitoring remain. More research is needed to fully elucidate the underlying mechanisms and optimize management strategies. Conclusion: Hypothyroidism during pregnancy represents a significant clinical challenge, but adequate administration of levothyroxine sodium can mitigate many of the associated risks. However, careful monitoring and additional research are essential to better understand and fully address the impacts of this condition on pregnancy and fetal development.